Robust superhydrophobic film on aluminum alloy prepared with TiO2/SiO2-silane composite film for efficient self-cleaning, anti-corrosion and anti-icing. (March 2023) - Han, Jianhua; Liu, Enhong; Zhou, Yuqin; Zhao, Shuang; Yan, Huiyu; Hu, Chenxi; Kang, Jianhai; Han, Qi; Su, Yuyu
Abstract: The stable superhydrophobic coating is significant for prolonging service life, reducing maintaining cost and enhancing material performances. In this study, robust superhydrophobic film was fabricated on Al alloy through anodic anodization followed by chemical deposition and spin coating of TiO2 /SiO2 -silane composite film. This fabrication method is controllable, eco-friendly, available for large and irregular Al alloy with low equipment requirements. Uniquely, the as-prepared Al alloy showed uniform micro-nanoporous arrays and achieved excellent superhydrophobic performance, with static water contact angle of 165º and sliding angle of 2.92º. Moreover, the robust superhydrophobic film on Al alloy presented high adhesion strength, strong stability under ambient air, ultraviolet light irradiation and abrasion. Meanwhile, two orders of magnitude reduction in corrosion current density and anti-corrosion efficiency of 99.2% were realized. The superhydrophobic Al alloy surface further displayed superb non-sticking, water repellency, self-cleaning, and anti-icing performances, which can be applied at harsh conditions in aerospace and marine fields. Graphical Abstract: ga1